Weryfikacja metod analizy ryzyka ekstremalnego na polskim rynku walutowym - Pietrzyk, Radosław (Verification of Methods of Extremal Risk Analysis in the Polish Exchange Market, 2007)
In this paper a study on tail index estimation has been carried out. Extreme daily changes in Polish exchange market are estimated using the peaks over threshold method. The parameters of Generalized Pareto distribution are estimated using maximum likelihood estimation. The peaks over threshold method provides a simple tool for estimating tail-related risk measures and may be useful in risk analysis of exchange rates. This method has been verified on Polish market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 551-559